2014
DOI: 10.1007/s10554-014-0518-5
|View full text |Cite
|
Sign up to set email alerts
|

Radial access during percutaneous interventions in patients with acute coronary syndromes: should we routinely monitor radial artery patency by ultrasonography promptly after the procedure and in long-term observation?

Abstract: Access-site vascular complications in patients undergoing transradial coronary procedures are rare but may have relevant clinical consequences. The aim of the study was to evaluate: (1) radial artery’s (RA) patency immediately after the procedure and in long-term observation, (2) factors influencing the frequency of radial artery’s occlusion (RAO) after percutaneous coronary intervention (PCI) procedures performed via transradial access in the group of 220 patients with acute coronary syndromes (ACS). RA ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
1
15
0
6
Order By: Relevance
“…Several studies evaluated significant predictors of RAO (Table ). Age was reported to be a significant predictor of RAO in 3 studies, while sex was significant in 6 studies . Body weight was reported as a significant predictor in 3 studies .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies evaluated significant predictors of RAO (Table ). Age was reported to be a significant predictor of RAO in 3 studies, while sex was significant in 6 studies . Body weight was reported as a significant predictor in 3 studies .…”
Section: Resultsmentioning
confidence: 98%
“…Age was reported to be a significant predictor of RAO in 3 studies, 47,77,78 while sex was significant in 6 studies. 29,49,69,73,77,78 Body weight was reported as a significant predictor in 3 studies. 17,65,75 In terms of procedural variables, use of a smaller introducer sheath has been shown to be predictive of lower RAO 71 and use of larger diameter of sheath 42,78,81 and duration of compression 61,81 was associated with higher occlusion rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transradial coronary procedures are increasingly being used. lisowska et al [16] studied 220 patients with acute coronary syndromes who underwent percutaneous coronary intervention performed via transradial access and studied radial artery's patency immediately after the procedure and in long-term observation using ultrasound technology. radial artery's occlusion was found in 15 % of the patients immediately after the procedure.…”
Section: Radial Artery Monitoring By Ultrasound After Transradial Cormentioning
confidence: 99%
“…Lisowka et al found that when ultrasound was used to evaluate radial artery patency 6-12 month following radial access, a not insignificant 15% had asymptomatic radial artery occlusion, and multivariable analysis demonstrated duration of the procedure as the main variable associated with arterial occlusion. 3 Levin et al reported a vessel closure in one of five patients treated with a radial artery 7-french sheath with a mean follow up of 507 days. 4 Performing peripheral PAD procedures from the radial artery has demonstrated an unflattering 31% occlusion rate in one published series.…”
mentioning
confidence: 99%